Radiocarbon dates : from samples funded by English Heritage and dated before 1981 - Jordan, David (Professor); Haddon-Reece, David; Bayliss, Alex (English Heritage, 1994)
"This volume holds a datelist of radiocarbon determinations carried out between 1970 and 1982 on behalf of the Ancient Monuments Laboratory, now part of English Heritage. It also contains supporting information about the samples and the sites producing them, a comprehensive bibliography, and three indexes for reference and analysis. The datelist has been collated to give access to a large body of information which, although mostly published elsewhere, has never before been accessible in a consistent form. When these dates were produced, high-precision calibration was not possible; now that this is available all dates have been converted, thus giving archaeologists and others using radiocarbon dates the opportunity to review their dating results in the light of this calibration, and with hindsight. The indexes order the complex information contained in the datelist by HAR numbers and by true calendar dates"--JSTOR website